Strong Induced Circular Dichroism in a Hybrid Lead‐Halide Semiconductor Using Chiral Amino Acids for Crystallite Surface Functionalization. Issue 14 (17th June 2022) - Heindl, Markus W.; Kodalle, Tim; Fehn, Natalie; Reb, Lennart K.; Liu, Shangpu; Harder, Constantin; Abdelsamie, Maged; Eyre, Lissa; Sharp, Ian D.; Roth, Stephan V.; Müller‐Buschbaum, Peter; Kartouzian, Aras; et al.
Abstract: Chirality is a desired property in functional semiconductors for optoelectronic, catalytic, and spintronic applications. Here, introducing enantiomerically‐pure 3‐aminobutyric acid (3‐ABA) into thin films of the 1D semiconductor dimethylammonium lead iodide (DMAPbI3 ) is found to result in strong circular dichroism (CD) in the optical absorption. X‐ray diffraction and grazing incidence small angle X‐ray scattering (GISAXS) are applied to gain molecular‐scale insights into the chirality transfer mechanism, which is attributed to a chiral surface modification of DMAPbI3 crystallites. This study demonstrates that the CD signal strength can be controlled by the amino‐acid content relative to the crystallite surface area. The CD intensity is tuned by the composition of the precursor solution and the spin‐coating time, thereby achieving anisotropy factors ( g abs ) as high as 1.75 × 10 –2 . Grazing incidence wide angle scattering reveals strong preferential ordering that can be suppressed via tailored synthesis conditions. Different contributions to the chiroptical properties are resolved by a detailed analysis of the CD signal utilizing an approach based on the Mueller matrix model. This report of a novel class of chiral hybrid semiconductors with precise control over their optical activity presents a promising approach for the design of circularly polarized light detectors and emitters. Abstract : Chiral amino acids are used to modify a 1D lead halide semiconductor via a simple spin‐coating approach. This results in circular dichroism effects within the material. In‐situ optical spectroscopy and X‐ray based diffraction and scattering techniques are utilized to understand and optimize these effects, resulting in extensive control over the material's optical properties.